Analysis of Diarrhea-Prone Area Mapping in West Java Province in 2023 - Prabawa, Artha; Wahyudi, Tri (Disease Prevention and Public Health Journal, 2025)
Background: West Java is one of the provinces with the highest prevalence of diarrhea. In 2023, the province reported 1,346,230 diarrhea cases of all age groups. Mapping high-risk areas for diarrhea will help in decision-making for the implementation of prevention and control efforts. Methods: This is a descriptive study using secondary data from Open Data Jabar 2023. The analysis was conducted to produce maps showing the distribution of dependent and independent variables, as well as the level of diarrhea risk in each district/city through scoring of all independent variables. Results: Out of 27 districts/cities, 6 were categorized as very high-risk and 3 as high-risk, with the highest scored variables were drinking water facilities, access to proper sanitation and stopping open defecation. However, when the risk levels were compared with the number of diarrhea cases, some districts/cities with low risk reported high and very high numbers of diarrhea cases, while some with very high risk had relatively low case numbers. Conclusion: The analysis shows that in 2023, about one-third districts/cities in West Java fall into the at-risk category for diarrhea. Prevention efforts should be focused on districts/cities with high risk. Further studies are needed to understand the role of other risk factors, as there is an inconsistency between risk levels and reported cases in several districts/cities.